EFEKTIVITAS MEDIA ONLINE OFFICE 365 UNTUK PEMBELAJARAN PKN PADA MASA PANDEMI COVID-19 DI SMK NEGERI 1 PEKANBARU - Nurul Nabila; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to find out the effectiveness of Office 365 online media for Civic Education learning during the pandemic covid-19. This study was conducted on students who had done PKn learning using Office 365 online media and students who had never learned using Office 365 (conventional) online media with a population of 882 people and a sample of 72 people determined using Isaac and Michael tables. The data collection method uses questionnaires to determine the use of Office 365 online media, documents of learning achievement to determine student learning achievement before using Office 365 online media and after using Office 365 online media and library studies are used to measure the effect oftovotas and theories in research. The data analysis techniques in this study are descriptive analysis in the form of questionnaire data to determine the use of Office 365 media and learning achievement to find out student learning achievement and t-paired sample t test to determine differences in learning outcomes and n-gain scores to currify the effectiveness of using Office 365 using SPSS software version 22 and Microsoft Exel. The results showed that office 365 oline media usage was good with a percentage gain of 44.44%, there is an increase in learning achievement After using Office 365, differences in learning achievement before using Office 365 and After using Office 365, and office 365 online media is quite effectively used as an online learning media for learning Civic Education learning the Pandemic covid-19 in SMK Negeri 1 pekanbaru with the acquisition of n-gain score of 67.14 based on hake theory (1999).Key Words: Effectiveness, Online Media Office 365, Pkn, Covid-19, Students